2012
DOI: 10.3171/2012.6.focus12194
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative neuromonitoring techniques in the surgical management of acoustic neuromas

Abstract: Unfavorable outcomes such as facial paralysis and deafness were once unfortunate probable complications following resection of acoustic neuromas. However, the implementation of intraoperative neuromonitoring during acoustic neuroma surgery has demonstrated placing more emphasis on quality of life and preserving neurological function. A modern review demonstrates a great degree of recent success in this regard. In facial nerve monitoring, the use of modern electromyography along with improvements in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 144 publications
(281 reference statements)
0
42
0
1
Order By: Relevance
“…Further studies showed that tumor volume was related with the effect of operation13,18,22,25,26). The foreign bulk case studies5,6) displayed that if the tumors were smaller, the postoperative facial nerve function was better.…”
Section: Discussionmentioning
confidence: 97%
“…Further studies showed that tumor volume was related with the effect of operation13,18,22,25,26). The foreign bulk case studies5,6) displayed that if the tumors were smaller, the postoperative facial nerve function was better.…”
Section: Discussionmentioning
confidence: 97%
“…Finden sich stark adhärente Nerven in der Vestibularisschwannomchirurgie, können aber auch bei nur noch geringen Gewebsschichten Stimulationen notwendig sein, die in der Ausdehnung dickere Gewebsschichten zwischen Stimualtionssonde und Nervus facialis erwarten lassen [ 286 ] . [ 280 ] . So wurde berichtet, dass nach der zusätzli-chen intra-und postoperativen Anwendung vasoaktiver Medikamente im Rahmen der Vestibularisschwannomchirurgie das Hörvermögen bei doppelt so vielen Patienten erhalten werden konnte wie ohne zusätzliche medikamentöse Therapie [ 306 ] .…”
Section: Nervenmonitoring Im Rahmen Der Vestibularisschwannomchirurgieunclassified
“…Morbidity was clearly reduced after introduction of intraoperative monitoring into VS surgery [279]. It allows the surgeon to adjust the treatment of VS in a way that allows optimal maintenance of CN function: (i) complete tumour resection, (ii) near-total resection or (iii) a combination of resection and postoperative radiosurgery [280], [281], [282].…”
Section: Selected Surgical Proceduresmentioning
confidence: 99%
“…Second, its function may be affected by vascular injury within the internal auditory canal during tumour resection (e.g. vascular occlusion, rupture or spasm) [279]. Accordingly, vasoactive treatment following VS surgery has been associated with a significantly higher rate of hearing preservation [305].…”
Section: Selected Surgical Proceduresmentioning
confidence: 99%